Literature Review: Pengaruh PMT Pangan Lokal Pada Balita sebagai Upaya Pencegahan Stunting - Restu Ayu Lestari; Ratih Kurniasari Kurniasari (SEHATI: Jurnal Kesehatan, 2024)
The high prevalence of stunting is a global problem of great concern. Efforts to reduce stunting are to provide additional food to children locally to improve their nutritional status. The purpose of making this literature review is to find out the effectiveness, influence, success of the program, and efforts to provide additional food to stunted toddlers. This literature review uses several sources, namely Sinta accredited journals related to supplementary feeding which can be searched using google scholar and the SINTA database. Based on the findings of 16 studies of supplementary feeding made from local food in stunted toddlers, there was an increase in body weight and height when supplementary feeding was given for at least 30 days. Tempeh, rebon shrimp, and moringa are local foods that are easily available and relatively cheap. They also have high nutritional value. After being given tempe, rebon shrimp, and moringa, as local foods, the toddler's height increased significantly.